2006
DOI: 10.4049/jimmunol.176.11.6434
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced TNF Receptor Family Related Gene Activation Overcomes Tolerance/Ignorance to Melanoma Differentiation Antigens and Enhances Antitumor Immunity

Abstract: Glucocorticoid-induced TNF receptor family related protein (GITR) is present on many different cell types. Previous studies have shown that in vivo administration of an anti-GITR agonist mAb (DTA-1) inhibits regulatory T cells (Treg)-dependent suppression and enhances T cell responses. In this study, we show that administration of DTA-1 induces >85% tumor rejection in mice challenged with B16 melanoma. Rejection requires CD4+, CD8+, and NK1.1+ cells and is dependent on IFN-γ and Fas ligand and independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
167
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(186 citation statements)
references
References 41 publications
17
167
1
1
Order By: Relevance
“…22,24,[26][27][28][29][30] These reports, which show enhancement of tumor responses using anti-GITR mAb delivered systemically, use 0.5-1 mg of mAb to see an anti-tumor effect, and studies in poorly immunogenic and very aggressive tumor models such as B16 melanoma routinely use 1 mg of anti-GITR mAb. 22,24,26,28 Mice were implanted with B16/F10.9 tumor cells and immunized once with TRP-2 RNA-transfected DC in conjunction with either DC transfected with control IgG RNA or anti-GITR H þ L RNA. Alternatively, mice were immunized with TRP-2 RNA-transfected DC in conjunction with 1 mg of control antibody or anti-GITR mAb injected intraperitoneally.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,24,[26][27][28][29][30] These reports, which show enhancement of tumor responses using anti-GITR mAb delivered systemically, use 0.5-1 mg of mAb to see an anti-tumor effect, and studies in poorly immunogenic and very aggressive tumor models such as B16 melanoma routinely use 1 mg of anti-GITR mAb. 22,24,26,28 Mice were implanted with B16/F10.9 tumor cells and immunized once with TRP-2 RNA-transfected DC in conjunction with either DC transfected with control IgG RNA or anti-GITR H þ L RNA. Alternatively, mice were immunized with TRP-2 RNA-transfected DC in conjunction with 1 mg of control antibody or anti-GITR mAb injected intraperitoneally.…”
Section: Resultsmentioning
confidence: 99%
“…13,14,21 An antibody that has been extensively tested in mice targets the glucocorticoid-induced tumor necrosis factor receptor (GITR). [22][23][24][25][26][27][28] GITR, a member of the tumor necrosis factor receptor superfamily, is constitutively expressed on Tregs but it is also expressed at low levels on multiple immune cells, including T cells, natural killer cells and B cells in which it is upregulated on activation. 7,23,[29][30][31] Treatment of mice with an agonistic anti-GITR mAb (anti-GITR), clone DTA-1, alone has been shown to cause exacerbated autoimmune disease in susceptible mice and enhanced anti-viral and anti-tumor immune responses in disease-bearing animals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[9][10][11][12][13][14] Interestingly, hsGITRL displays biological activity by forming multiple oligomerization. 16 The ILZ motif has been shown to form trimers in solution and many soluble TNF/TNF receptor superfamilies modified by an ILZ motif can form stable trimeric or multiple oligomerization states.…”
Section: Discussionmentioning
confidence: 99%
“…GITR triggered by soluble GITRL, cell surface GITRL or anti-GITR monoclonal antibody (mAb) (DTA-1) abrogates regulatory Tcell suppression 3,4,7,8 and results in exacerbation of organ-specific autoimmune diseases, 3,9,10 , enhancement of antitumor immunity and the immunity to viral pathogens. [11][12][13] Thus, the functional interaction between GITR and GITRL is important for regulatory T cells to induce immune tolerance and regulate homeostasis. 14,15 Structure analysis has revealed that human soluble GITRL (hsGITRL) increases its receptor-binding affinity and enhances costimulatory activity through self-assembly into a trimer.…”
Section: Introductionmentioning
confidence: 99%